The Role of Modern Geodetic Equipment in Topographic Works - Karimov , Fakhriddin (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
Topographic mapping has fundamentally transformed from discrete point measurements to continuous spatial data acquisition. This thesis comparatively evaluates the economic and metrological efficiency of traditional total stations against automated measurement complexes (GNSS, RTK, LiDAR, UAV). Field tests were conducted on a 450-hectare site with complex terrain utilizing traditional polygonometry (Leica FlexLine TS07) and an integrated digital approach (Trimble R12i GNSS, DJI Matrice 300 RTK). Results demonstrated that modern equipment reduced surveying time per hectare from 8.4 to 0.35 hours. The Digital Elevation Model (DEM) generated via laser scanning achieved a density of 450-500 points per square meter, reflecting the morphological features of the terrain with absolute precision. Implementing innovative geodetic tools exponentially minimizes labor costs while establishing a reliable spatial foundation for Smart City and BIM infrastructures.